2015
DOI: 10.1177/1753944715598714
|View full text |Cite
|
Sign up to set email alerts
|

Drug coated balloon angioplasty in elderly patients with small vessel coronary disease

Abstract: DBCA in the elderly with SVCD is as safe and effective compared with younger patients despite more complex anatomy and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Compared to the SeQuent Please World Wide Registry [39], the slightly higher clinical event rates seen in the SeQuent Please Small Vessel “PCB Only” Registry are probably explained by the smaller reference vessel diameter in this study, as also suggested by the authors [35]. From the SeQuent Please Small Vessel “PCB Only” Registry, three substudies have been reported focusing on the DEB-only strategy for elderly patients (≥75 years) [43], patients with acute coronary syndrome [44], and Asian vs. Western patients [45]. These studies are presented in Table 3.…”
Section: Drug-eluting Balloonsmentioning
confidence: 59%
See 2 more Smart Citations
“…Compared to the SeQuent Please World Wide Registry [39], the slightly higher clinical event rates seen in the SeQuent Please Small Vessel “PCB Only” Registry are probably explained by the smaller reference vessel diameter in this study, as also suggested by the authors [35]. From the SeQuent Please Small Vessel “PCB Only” Registry, three substudies have been reported focusing on the DEB-only strategy for elderly patients (≥75 years) [43], patients with acute coronary syndrome [44], and Asian vs. Western patients [45]. These studies are presented in Table 3.…”
Section: Drug-eluting Balloonsmentioning
confidence: 59%
“…The authors noticed that the results are comparable with the everolimus-eluting stent from the SPIRIT Small Vessel trial that reported a clinically indicated TLR of 5.1% after 1 year [78]. The recommendation for DAPT treatment was 1 month, and most of the patients received DAPT for this period with a small proportion exceeding it [43]. As older people in general are more at risk of complications with prolonged DAPT treatment, this study showed a low 6.1% MACE after 9 months despite the shortened DAPT duration, highlighting the tempting aspects of DEB treatment and thereby avoidance of prolonged DAPT treatment in the elderly patients.…”
Section: Drug-eluting Balloonsmentioning
confidence: 94%
See 1 more Smart Citation
“…Drug‐coated balloons (DCB) have recently emerged as a potential therapeutic strategy for patients with small vessel de novo coronary artery disease, even in the setting of primary angioplasty . DCB allow rapid and uniform tissue delivery of paclitaxel to the lesion of interest and is an established treatment modality for in‐stent restenosis .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, small coronary arteries (<2.5 mm) remain a particular challenge with high rates of stent failure due to late lumen loss (LLL) and may predict both repeat revascularization and subsequent adverse events. 5 Drug-coated balloons (DCB) have recently emerged as a potential therapeutic strategy for patients with small vessel de novo coronary artery disease, 6,7 even in the setting of primary angioplasty. 8 DCB allow rapid and uniform tissue delivery of paclitaxel to the lesion of interest and is an established treatment modality for in-stent restenosis.…”
Section: Introductionmentioning
confidence: 99%